Insulin hypersensitivity induced by hepatic PTEN gene ablation protects from murine endotoxemia. - Philipp M Guenzl; Roman Raim; Julia Kral; Julia Brunner; Emine Sahin; Gernot Schabbauer (PLoS ONE)
Sepsis still remains a major cause for morbidity and mortality in patients. The molecular mechanisms underlying the disease are still enigmatic. A great number of therapeutic approaches have failed and treatment strategies are limited to date. Among those few admitted for clinical intervention, intensive insulin treatment has proven to be effective in the reduction of disease related complications in critically ill patients. Insulin effectively reduces glucose levels and thereby contributes to protection. On the other hand insulin is a potent signaling pathway activator. One of those is the PI3K signaling axis. Activation of PI3K is known to limit pro-inflammatory gene expression. Here we can show that in a mouse model of insulin hypersensitivity induced by the deletion of the PI3K antagonist PTEN, specifically in hepatic tissue, significant protection is conferred in murine models of lethal endotoxemia and sepsis. Acute inflammatory responses are diminished, glucose metabolism normalized and vascular activation is reduced. Furthermore we investigated the hepatic gene expression profile of relevant anti-inflammatory genes in PTEN deficient mice and found marked upregulation of PPARγ and HO-1. We conclude from our data that insulin hypersensitivity via sustained activation of the PI3K signaling pathway exerts protective effects in acute inflammatory processes.